A Formulasi ‘Zilang Tea” Teh Herbal Peningkat Imunitas Tubuh Berbahan Jahe Merah (Zingiber officinale var. Rubrum) dan Bunga Telang (Clitoria ternatea): Formulation of 'Zilang Tea' Herbal Immunity Enhancing Tea Made from Red Ginger (Zingiber officinale var. Rubrum) and Telang Flower (Clitoria ternatea) - Agustin Wijayanti (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2022)
Zilang Tea is a herbal tea formulated by the PKM Kewirausahaan Team at the Bhakti Setya Health Polytechnic Indonesia. The herbs are in the form of teabags made from telang flower and dried red ginger. The purpose of this herbal formulation is to increase the selling value of telang flower and red ginger and to make practical herbal tea preparations that contain active compounds to increase body immunity. The process of making this herbal tea starts from sorting, washing, chopping to drying by following the simplicia drying instructions from previous studies. Furthermore, the smoothing of simplicia is carried out. The refined simplicia was then weighed and mixed according to the selected formula and then packaged. Herbal tea products that have been packaged can be consumed by brewing in hot water. The active compound in the form of Vitamin C, various types of flavonoids dissolved in it can have efficacy as an immunostimulant to increase the activity of the immune system against viruses, bacteria and other microbes. The results of steeping herbal teas are purple like the color of telang flowers and have a slightly spicy taste like ginger. The conclusion of this formulation is the use of telang flower and red ginger to be used as herbal tea bags as potential health drinks to be utilized and developed by the wider community.